2017
DOI: 10.1007/s00497-017-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic analysis of tomato pollen development and heat stress response

Abstract: Key message Pollen development metabolomics. AbstractDeveloping pollen is among the plant structures most sensitive to high temperatures, and a decrease in pollen viability is often associated with an alteration of metabolite content. Most of the metabolic studies of pollen have focused on a specific group of compounds, which limits the identification of physiologically important metabolites. To get a better insight into pollen development and the pollen heat stress response, we used a liquid chromatography–ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 74 publications
3
68
0
Order By: Relevance
“…Several studies have suggested that flavonols are part of the heat-stress response in vegetative and reproductive tissues. Indeed, transcript abundances and enzyme activities of flavonol biosynthetic genes (39), as well as flavonol pools (39,42), increase during heat stress in tomato leaves and pollen grains. Therefore, we analyzed the effect of acute heat stress on tomato pollen tube growth and ROS levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that flavonols are part of the heat-stress response in vegetative and reproductive tissues. Indeed, transcript abundances and enzyme activities of flavonol biosynthetic genes (39), as well as flavonol pools (39,42), increase during heat stress in tomato leaves and pollen grains. Therefore, we analyzed the effect of acute heat stress on tomato pollen tube growth and ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress increases ROS production, which results in distinct transcriptional responses (38), including increased abundance of transcripts and proteins involved in ROS scavenging (39)(40)(41). Elevated temperature has been shown to increase flavonol biosynthesis in vegetative tissues (39), as well as in developing pollen (42). However, the involvement of flavonols as antioxidants against high-temperature-induced ROS has not been reported.…”
Section: Significancementioning
confidence: 99%
“…Heat stress affects composition in the primary and secondary metabolites (carbohydrates, lipids, proline, polyamines, glutathione, and flavonoids) [14,28]. A decrease in pollen viability is often associated with an alteration of metabolite contents such as soluble sugars and starch [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…These tolerant types also produced low concentrations of many metabolites, such as chiro-inositol, pinitol, erythritol, and arabitol [157]. Metabolomics analysis was also performed for other important crops, such as tomato, maize, and wheat, to observe the effects of heat stress [158][159][160].…”
Section: Temperature Stress Regulationmentioning
confidence: 99%